Local recurrence after stenting for obstructing left‐sided colonic cancer. Issue 13 (December 2013) - Gorissen, K. J.; Tuynman, J. B.; Fryer, E.; Wang, L.; Uberoi, R.; Jones, O. M.; Cunningham, C.; Lindsey, I.
<x xml:space="preserve">Abstract</x> Background Self‐expanding metallic stents (SEMS) may be used in acute obstructing left‐sided colonic cancers to avoid high‐risk emergency surgery. However, oncological safety remains uncertain. This study evaluated the long‐term oncological outcome of SEMS as a bridge to elective curative surgery versus emergency resection. Methods A consecutive prospective cohort of patients admitted with obstructing left‐sided colonic cancer between 2006 and 2012 was analysed. The decision to stent as a bridge to surgery or to perform emergency surgery was made by the on‐call consultant colorectal surgeon in conjunction with a consultant interventional radiologist; when appropriate, they performed the stent procedure together. Primary outcomes were local and distant recurrence, and overall survival. Secondary outcomes were postoperative complications, in‐hospital mortality, proportion of procedures undertaken laparoscopically, and anastomosis and stoma rates. Results In total, 105 patients with obstructing left‐sided colonic cancer were treated with curative intent; 62 were treated with SEMS as a bridge to surgery and 43 had emergency resection. In patients aged 75 years or less, stenting and delayed surgery was associated with a higher local recurrence rate compared with emergency surgery at the end of follow‐up (32 versus 8 per cent; P = 0·038). This did not translate into a significant difference in overall survival. Conclusion SEMS was associated with an increased local recurrence rate.